Penerapan Prinsip Good Governance pada Pelaksanaan Keterbukaan Informasi Publik di Desa Batu Kajang Kecamatan Batu Sopang Kabupaten Paser - Ansyari, Farlian; Alim, Bimantara Nur; Angreni, Dyah Kuntorini Dwi (Universitas Syiah Kuala, 2025)
This study aims to analyze the implementation of good governance principles in the implementation of public information disclosure in Batu Kajang Village, Batu Sopang Sub-district, Paser Regency, East Kalimantan. Referring to Law No. 14/2008 on Public Information Disclosure, this study examines how the principles of transparency, accountability and participation are implemented in the context of village government. The approach used is descriptive qualitative with a case study strategy, where data is fully obtained through a literature study of official documents, government reports, trusted online news, and statutory regulations. The results showed that Batu Kajang Village has started the implementation of public information disclosure through digital channels such as the official village website that presents information about the APBDes, government structure, and development activities. Transparency is the most visible aspect, although the updating and completeness of information is still a challenge. Accountability is implemented through financial reporting and annual accountability meetings, but is not yet accompanied by adequate feedback mechanisms from the community. Community participation is facilitated through village meetings and DPRD recesses, but does not yet cover all levels of society, especially vulnerable groups. Meanwhile, PPID has been established in Batu Kajang Village, but still lacks a standard operating procedure that regulates the classification of information.